2010
DOI: 10.1093/bja/aeq022
|View full text |Cite
|
Sign up to set email alerts
|

Rotation thromboelastometry detects thrombocytopenia and hypofibrinogenaemia during orthotopic liver transplantation

Abstract: ROTEM is useful for the global assessment of coagulation in the operating theatre. EXTEM was the most informative for assessing the whole coagulation process and A10 showed value in guiding Plt and Fg transfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
94
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(100 citation statements)
references
References 22 publications
5
94
1
Order By: Relevance
“…This is in agreement with Roullet et al [81] who demonstrated that EXTEM A10 showed a good correlation to platelet count and plasma fibrinogen levels. The predictable threshold for thrombocytopenia (<50,000 mm -3 ) was reported as an EXTEM A10 < 29 mm and had a sensitivity and specificity of 79% and 60%, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with Roullet et al [81] who demonstrated that EXTEM A10 showed a good correlation to platelet count and plasma fibrinogen levels. The predictable threshold for thrombocytopenia (<50,000 mm -3 ) was reported as an EXTEM A10 < 29 mm and had a sensitivity and specificity of 79% and 60%, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Roullet et al [44] concluded that ROTEM ® is useful for the global evaluation of coagulation and the EXTEM was the most informative to evaluate the entire coagulation process. Therefore, the empirical use of blood products uncontrolled by ROTEM ® should not be considered in the current real evidence in the literature [45].…”
Section: Discussionmentioning
confidence: 99%
“…Thromboelastometry may provide an immediate assessment of the state of coagulation, help implement targeted treatment, and help minimize blood product transfusion during liver transplant. [28][29][30] In the present program, factors contributing to the significant decrease in cold ischemia time, operative time, and blood product transfusion (Table 3) included the use of thromboelastometry, increased experience, and performance of > 20 transplants per year.…”
Section: Discussionmentioning
confidence: 99%